2007
DOI: 10.1074/jbc.m610633200
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Cocaine Analog [125I]RTI 82 Irreversible Binding to Transmembrane Domain 6 of the Dopamine Transporter

Abstract: The site of cocaine binding on the dopamine transporter (DAT) was investigated using the photoactivatable irreversible cocaine analog [125 I]3␤-(p-chlorophenyl)tropane-2␤-carboxylic acid, 4-azido-3-iodophenylethyl ester ([ 125 I]RTI 82). The incorporation site of this compound was mapped to transmembrane domains (TMs) 4 -6 using epitope-specific immunoprecipitation of trypsin fragments and further localized using cyanogen bromide (CNBr), which hydrolyzes proteins on the C-terminal side of methionine residues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…Recently, it was shown that the photoreactive cocaine analog [ 125 I]RTI 82 incorporated into TMD 6 (ref. 17), which is an important part of the cocaine-binding site in the models presented here. Together with these previous findings, our results provide strong evidence that cocaine and its analogs are true competitive inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the photoreactive cocaine analog [ 125 I]RTI 82 incorporated into TMD 6 (ref. 17), which is an important part of the cocaine-binding site in the models presented here. Together with these previous findings, our results provide strong evidence that cocaine and its analogs are true competitive inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling and mutagenesis studies of cocaine and cocaine analog binding in hDAT predict that cocaine would interact significantly with hSERT TM6 residues (16,57,58). Specifically, hDAT residues Phe-320, Ser-321, and Leu-322, which correspond by homology to hSERT Phe-335, Ser-336, and Leu-337, are predicted to interact with the N-methylamine of (Ϫ)-2␤-carbomethoxy-3␤-(4-fluorophenyl)tropane (CFT), a cocaine analog, and thus, we predicted that the homologous hSERT residues would be protected by cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the existence of multiple binding sites for different inhibitors on DAT, and studies with irreversible ligands may be important in mapping these respective sites [24][25][26][27]. Both photoaffinity ligands [28][29][30] and alkylating reagents [31][32][33][34], including the tropane analog [ 125 I]RTI-82 [35], have been used to identify the ligand binding sites of cocaine and related tropane analogs on DAT. In addition, alkylating agents including isothiocyanate and bromoacetamide tagged to cocaine, rimcazole and benztropine analogs have been successful as irreversible DAT analogs [31,32,36].…”
Section: Introductionmentioning
confidence: 99%